БІОЛОГІЧНА НАУКА ТА НАВЧАЛЬНИЙ ПРЕДМЕТ: ПРОБЛЕМИ ВЗАЄМОЗВ’ЯЗКУ (Педагогіка вищої та середньої школи, 2007)
The article is devoted to problem of reflection a basic science in school subject. Characteristics of biology and school knowledge and cognition are distinguished. The ties between them are established. The question about their dynamic is considered for biological courses in 7-9 forms.